Coke formation during the hydrotreatment of bio-oil using NiMo and CoMo catalysts - Kadarwati, S.; Hu, X.; Gunawan, R.; Westerhof, R.; Gholizadeh, M.; Hasan, M.; Li, Chun-Zhu (Elsevier, 2016)
This study aims to investigate the coke formation during the hydrotreatment of bio-oil at low temperature. The catalytic hydrotreatment of bio-oil produced from the pyrolysis of mallee wood was carried out using pre-sulphided NiMo and CoMo catalysts at a temperature range of 150-300. °C. Our results show that the catalysts play an important role in reducing the coke formation. The transformation of light products during the hydrotreatment was investigated. The role of levoglucosan in the coke formation was investigated by adding additional levoglucosan into the bio-oil prior to the hydrotreatment. In the presence of the catalyst, the hydrotreatment of bio-oil with the added levoglucosan did not yield more coke than that of original bio-oil under identical conditions. However, in the absence of the hydrotreating catalyst, coke formation was intensified. Our data indicate that levoglucosan could cross-link with other compounds in bio-oil in the absence of a hydrotreatment catalyst.